228k views
1 vote
Rewrite the expression in terms of the given angle's reference angle; then evaluate the result. Write the exact answer. Do not round.sin1113

Rewrite the expression in terms of the given angle's reference angle; then evaluate-example-1
User Joemon
by
4.8k points

1 Answer

1 vote

Rewrite the angle inside the expression as:


(11\pi)/(3)=4\pi-(\pi)/(3)

Apply sine function on both sides and use the identity sin(A-B) = sin A cos B - cos A sin B.


\begin{gathered} \sin ((11\pi)/(3))=\sin (4\pi-(\pi)/(3)) \\ =\sin 4\pi\cos (\pi)/(3)-\cos 4\pi\sin (\pi)/(3) \\ =0\cdot\cos (\pi)/(3)-1\cdot\frac{\sqrt[]{3}}{2} \\ =-\frac{\sqrt[]{3}}{2} \end{gathered}

User Fbitterlich
by
5.3k points